(Un)Readiness of Bosnia and Herzegovina for the Challenges and Possible Threats from a Migrant Crisis - Grbić Pavlović, Nikolina; Pavlović, Gojko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The migrant crisis that hit the region's countries in previous years did not bypass Bosnia and Herzegovina. Official reports of institutions, year after year, indicate an increase in the number of irregular migrants discovered. For example, for the first five months of 2018, some measures were taken towards 3.177 citizens of countries with high migration risk. On the other hand, in the period from January 1 to December 31, 2017, in the attempt or immediately after the irregular border crossing, a total of 753 citizens of high migration risk countries were discovered, while fewer than a hundred were discovered in 2016. It is characteristic that migrants are more often in larger groups (10, 15, 30 to 50 people) trying to enter Bosnia and Herzegovina irregularly. Often, in these groups are also vulnerable categories (juveniles, women, pregnant women and the sick and exhausted people). This is why the goal of this paper is to show the capacity in Bosnia and Herzegovina related to counter the crisis. The author's intention is to try to answer the question: Is Bosnia and Herzegovina, with its legal and institutional capacity, ready to respond to the migrant crisis, or to all the challenges and possible threats that such a crisis brings with it? The authors point out that an active whole-of-society approach is needed to address migrant crises.